[Crystal Palace, 1851] : [design for a paper hanging] - National Archives (Great Britain); Adam Matthew Digital (Adam Matthew Digital, 2007)
Colour illustration of Crystal Palace at the time of the Great Exhibition, 1851. Electronic reproduction of the painting held at the National Archives